Empowerment Programs among Local Inhabitants at Rabak Residence in Indonesia - Roikhan Mochamad Aziz (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Community service in Rabak Village, Bogor, Indonesia, was done for 30 days, involving 16 students from 7 faculties with an additional 1 lecturer as a supervisor. Activities were conducted from August until September 2017. The approach used the methodology of Hahslm with the ontology of Islam, comprehensiveness in epistemology, and axiology of balancing. This guidance method utilized the straight path theory that combines the three main factors, internal, external, and reflexivities such as academicians, regulators, and ulama. For the planning and implementation, the research had objectives to map community potential, increase people capacity and transfer education. There were problems with local culture and obstacles encountered such as lack of time, sort of consolidating and coordinating with various parties in internal group members and supervisors, external parties such as sponsors, as well as the reflexivity of ulama and religious leaders. From the results of the activities, there were several successes: increasing community participation in development programs in villages, increasing motivation to learners in elementary and junior high school to continue education to higher levels, and to educate public knowledge about Islamic universities, to increase public awareness of the importance of marriage books, and increase physical building or development rehabilitation of water reservoirs, and reading parks.